Correction: An Improved Transplantation Strategy for Mouse Mesenchymal Stem Cells in an Acute Myocardial Infarction Model. - Jianliang Jin; Yingming Zhao; Xiao Tan; Chun Guo; Zhijian Yang; Dengshun Miao (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0021005.].